2015
DOI: 10.1111/1759-7714.12262
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of once daily radiotherapy to 60 Gy and twice daily radiotherapy to 45 Gy for limited stage small‐cell lung cancer

Abstract: BackgroundThis study was designed to compare toxicities, disease control, and survival outcomes for limited disease small-cell lung cancer (LD-SCLC) treated with once daily (QD) versus twice daily (BID) radiotherapy.MethodsAll of the patients received four to six cycles of platinum plus etoposide. In the QD group, irradiation was given via conventional radiotherapy with a dose of 60 Gy at 2 Gy per once-daily fraction. In the BID group, the dose was 45 Gy at 1.5 Gy per twice-daily fraction.ResultsData from a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 18 publications
0
30
0
1
Order By: Relevance
“…However, the optimal dose and fractionation for TRT in limited-stage SCLC remain controversial; a hyperfractionated regimen (45 Gy in 30 fractions delivered as 1.5-Gy fractions twice daily, BID group) or a conventionally fractionated regimen (60–70 Gy in 30–35 fractions delivered as 2.0-Gy fractions once daily, QD group) has been used in routine clinical practice. Pneumonitis and dermatitis were more common in the QD group, and esophagitis was more common in the BID group [ 24 , 25 ]. Possible differences in toxicities depending on RT regimen may be worth further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal dose and fractionation for TRT in limited-stage SCLC remain controversial; a hyperfractionated regimen (45 Gy in 30 fractions delivered as 1.5-Gy fractions twice daily, BID group) or a conventionally fractionated regimen (60–70 Gy in 30–35 fractions delivered as 2.0-Gy fractions once daily, QD group) has been used in routine clinical practice. Pneumonitis and dermatitis were more common in the QD group, and esophagitis was more common in the BID group [ 24 , 25 ]. Possible differences in toxicities depending on RT regimen may be worth further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The abstracted radiotherapy data included technique, as well as fractionation, overall treatment time and dose from which a biological equivalent dose was calculated. The BED was calculated from the formula: ( nd )[1+ d /( α / β )]–(0.693 t / αT pot), where n =the total number of fractions delivered; d =the dose per fraction (Gy); α / β =10 for acute effects and tumour control and three for late effects; α =0.3 Gy −0 ; t =total days in which RT was delivered; and T pot=potential doubling time (5.6 days) ( Han et al , 2015 ). Follow-up and cause of death were based on the medical chart or electronic data from either the Ontario Cancer Registry or the Ontario Registrar General.…”
Section: Methodsmentioning
confidence: 99%
“…Only 1 of the 5 included studies reported the objective response rate (ORR). [ 15 ] Three out of 5 studies reported LRFS-related data (1 or more of the 1-year LRFS rate, 2-year LRFS rate, 5-year LRFS rate, mLRFS, and LRFS Kaplan–Meier curves), [ 13 , 15 , 16 ] 3 reported PFS-related data (1 or more of the 1-year PFS rate, 2-year PFS rate, 5-year PFS rate, mPFS, and PFS Kaplan–Meier curves), [ 13 , 15 , 16 ] 4 reported radiation toxicity (both esophagitis and pneumonitis), [ 13 , 15 , 16 , 23 ] and all 5 included studies reported OS-related data (1 or more of the 1-year OS rate, 2-year OS rate, 5-year OS rate, mOS, and OS Kaplan–Meier curves). [ 13 16 , 23 ] Since pooled data of 60 to 72 Gy RT with 1.8 Gy/2 Gy once daily vs 45 Gy RT with 1.5 Gy twice daily were not reported, data from Davids study [ 14 ] were included in this analysis in 2 independent parts (60–61.2 Gy/1.8–2 Gy once-daily vs 45 Gy/1.5 Gy twice-daily, and 62–72 Gy/1.8–2 Gy once-daily vs 45 Gy/1.5 Gy twice daily) and were analyzed independently as if they were from 2 different studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 3 studies that reported the PFS-related data, [ 13 , 15 , 16 ] 2 reported the 1-year PFS rate, [ 15 , 16 ] 2 reported the 2-year PFS rate, [ 15 , 16 ] 2 reported the 5-year PFS rate, [ 15 , 16 ] and 3 reported the mPFS. [ 13 , 15 , 16 ] No heterogeneity was found between the 2 studies [ 15 , 16 ] that reported the 1-year PFS rate ( P = .681, I 2 = 0%); therefore, a fixed-effects model was applied. No significant increase in the 1-year PFS rate was found in the twice-daily thoracic RT arm compared with the higher-dose once-daily RT arm (OR 0.77, 95% CI: 0.44–1.38, P = .384, Fig.…”
Section: Resultsmentioning
confidence: 99%